2010
DOI: 10.1002/pola.24247
|View full text |Cite|
|
Sign up to set email alerts
|

Facile, one‐pot synthesis of aromatic diamine‐based phosphinated benzoxazines and their flame‐retardant thermosets

Abstract: Three aromatic diamine‐based, phosphinated benzoxazines (7–9) were prepared from three typical aromatic diamines—4,4′‐diamino diphenyl methane (1), 4,4′‐diamino diphenyl sulfone (2), and 4,4′‐diamino diphenyl ether (3) by a one‐pot procedure. To clarify the reaction mechanism, a two‐pot procedure was applied, in which the reaction intermediates (4–6) were isolated for characterization. The structures of intermediates and benzoxazines were confirmed by high resolution mass, IR, and 1D and 2D‐NMR spectra. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…1,4-phenylenediamine 60 g (0.55 mol), finely powdered, was then added into the beaker and immersed in an oil bath preheated at 140°C. The addition of the diamine leads to the gelation of the mixture resulting from the condensation of the aromatic diamine and formaldehyde and the subsequent formation of a triazine network [30,31]. At this temperature, the triaza compound reacts quickly with phenol and the gel is destroyed in 2 min.…”
Section: Preparation and Characterization Of P-ppda Precursormentioning
confidence: 98%
“…1,4-phenylenediamine 60 g (0.55 mol), finely powdered, was then added into the beaker and immersed in an oil bath preheated at 140°C. The addition of the diamine leads to the gelation of the mixture resulting from the condensation of the aromatic diamine and formaldehyde and the subsequent formation of a triazine network [30,31]. At this temperature, the triaza compound reacts quickly with phenol and the gel is destroyed in 2 min.…”
Section: Preparation and Characterization Of P-ppda Precursormentioning
confidence: 98%
“…4,5 It has been reported that phosphorus-containing compounds able to molecularly incorporate in the resin network are expected to exhibit better flame retardancy. [6][7][8][9][10] As a typical flame retardant (FR) with active phenolic OH groups, 2-(6-oxid-6H-dibenz[c,e][1,2]-oxaphosphorin-6-yl)-1,4-benzenediol embody this incorporation strategy. 11 Another approach to realize this strategy is based on the addition reactions of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and imines, whose products are characteristic of binary functionality of FR and co-curing agent.…”
Section: Introductionmentioning
confidence: 99%
“…DOPO and its derivatives not only could be used as reactive and additive flame retardant, but also could be used in linear polyester, polyamide, epoxy resin, polyurethane, and other polymer flame retardant processed . Lin prepared three aromatic diamine‐based, phosphinated benzoxazines from three typical aromatic diamines‐4,4′‐diamino diphenyl methane, 4,4′‐diamino diphenylsulfone, and 4,4′‐diamino diphenyl ether by a one‐pot procedure. The results demonstrated that these materials offered high thermal stability and good flame retardancy …”
Section: Introductionmentioning
confidence: 99%